1967
DOI: 10.1128/jb.93.3.1119-1131.1967
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Mycobacterium lepraemurium in Cultures of Mouse Peritoneal Macrophages

Abstract: Successful growth of Mycobacterium lepraemurium was observed in cultures of mouse peritoneal macrophages. The optimal host cell maintenance medium was composed of 40% horse serum, 50% of the chemically defined medium NCTC 109, and 10% of a 1: 5 dilution of beef embryo extract, supplemented with both liver extract and ferric nitrate. Multiplication of the bacilli was observed in 1 week and maximal growth in 6 to 7 weeks. All macrophages were filled with tens to hundreds of the organisms in cultures showing maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
1

Year Published

1968
1968
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…However, some bacteria at-clusters in different numbers were observed days in the Leighton tube culture. These results are not as rapid as those reported by Rees and Garbutt [8] who noted an average generation time of 15 days, and Clung, Anderson, and Vaituzis [2] with their results of 7 days.…”
Section: Resultscontrasting
confidence: 47%
See 4 more Smart Citations
“…However, some bacteria at-clusters in different numbers were observed days in the Leighton tube culture. These results are not as rapid as those reported by Rees and Garbutt [8] who noted an average generation time of 15 days, and Clung, Anderson, and Vaituzis [2] with their results of 7 days.…”
Section: Resultscontrasting
confidence: 47%
“…Chang and his associates [2] studied on the effect of mycobactin, glycerol, liver extract, liver homogenate, ferric nitrate, and various combinations of these substances, and found that liver homogenate, liver extract, and ferric nitrate, and combination of L-fraction of liver or iron and glycerol had definite stimulatory effects on the growth of M. lepraernuriurn. Addition of other substances which might be found useful for promoting the growth of this organism will also be examined in future experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations